Persepsi Nilai-Nilai Budaya pada Kembar Mayang Bagi Pasangan Generasi Milenial Desa Geger Kecamatan Sendang - Khusnul Khotimah; Ahmad Nurcholis (Medina-te : Jurnal Studi Islam, 2022)
The purpose of this study to describe, analyze, and interpret the perception of cultural values ​​in the ritual of the Mayang Twins. The type of research used is qualitative with phenomenological analysis methods. The grand theory in this study uses the theory of symbolic interactionism which was initiated by George Herbert Mead in 1934. Where he stated that the theory of symbolic interactionism sees the mind and self as part of human behavior that is part of interaction with other people. Interaction makes humans know the world and themselves. The results of this study prove that the millennial generation's perception of mayang twins appears after they experience and witness firsthand during the wedding procession. Mayang twins have a meaning as a symbol of obtaining off spring marked by the ngekarne "blooming" ritual. There is a symbolic interaction during the process of making mayang twins.